Evaluation of the Antiplasmodial Properties of Andrographis paniculata (Burm.f.) and Peperomia pellucida (L.) Kunth - Nurhayati Bialangi; Mohamad Adam Mustapa; Yuszda Salimi; Weny Musa; Ari Widiyantoro; Agus Malik Ibrahim; Boima Situmeang; Julinton Sianturi (Universitas Gadjah Mada, 2023)
Plasmodium species are the infectious agents that are responsible for malaria, a disease that claims the lives of approximately 400,000 people annually. The fact that drug resistance against malaria is on the rise suggests that new antimalarial compounds need to be discovered. It is well known that medicinal plants present the best opportunity for the identification of novel antimalaria chemicals. Both the Andrographis paniculata (Burm.f.) and Peperomia pellucida (L. Kunth) species have been tested for their antiplasmodial ability against the Plasmodium falciparum strain. The P. pellucida (L. Kunth) species has also been subjected to in vitro and in vivo biological research. P. pellucida was used to isolate the steroid known as 3-hydroxy-24-ethyl-5,22-cholestadiene (1) and the triterpenoid known as 3-hydroxy-9-lanosta-7,24E-dien-26-oic acid (2). Both compounds were then tested for their activity in vitro. In the mice model, triterpenoid 2 had a substantial chemo-suppressive impact.